The Design of Wild Animals Monitoring System Based on 3G and Internet of Things - Jiang Xiao; Chenying Zeng; Zhouyan Yu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
As the rapid growth of economy and population, the wild animals’ habitat is badly damaged by the development and utilization of wild animals living environment by people. To carry out the research on wildlife monitoring technology is of great significance. Along with the advent of the era of 3G, 3G transmission technology is more and more advanced, and the Android operating system is currently the most popular operating system. The advantages and disadvantages of the existing monitoring technology are summed up, then wireless multimedia sensor network monitoring technology solutions which is a collection of 3G technology, Android platform and Zigbee short-range wireless communication technology is put forward in this paper. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3895